Choroid plexus tumors: A clinico-pathological and neuro-radiological study of 23 cases - Jaiswal, Sushila (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Choroid plexus tumors are intraventricular tumors derived from choroid plexus epithelium. AIM: To study the choroid plexus tumors with reference to their clinical, radiological, and pathological features. MATERIALS AND METHODS: The study was performed by the retrospectively reviewing the clinical, radiological, and pathological records of patients of choroid plexus tumors. RESULTS: A total of 23 cases (11 males, 13 females) of choroid plexus tumor were diagnosed from 1997 to 2009. Fourteen patients were below 15 years of age. Raised intracranial pressure was the main presenting feature in all the cases. Tumor was located in lateral ventricle (n = 14; in 3 cases tumor was going into third ventricle), fourth ventricle (n = 7), and cerebellopontine angle (n = 2). Total tumor excision was achieved in 21 cases. The histopathology was suggestive of choroid plexus papilloma (n = 19), atypical choroid plexus papilloma (n = 1), and choroid plexus carcinoma (n = 2). Clears cell areas were noted in three cases. Other histopathological features observed were foci of calcification (n = 5), Psammoma bodies (n = 2), hemorrhage (n = 5), hyalinization (n = 2), and oncocytic changes (n = 1). CONCLUSIONS: Choroid plexus tumors are intraventricular tumors arising from choroid plexus epithelium. The predominant clinical presentation is raised intracranial pressure. Surgery is the mainstay of treatment; histopathologically, they include choroid plexus papilloma, atypical choroid plexus papilloma, and choroid plexus carcinoma.